Determining Zygosity With Multiplex Kompetitive Allele‐Specific PCR (mxKASP) Genotyping - Willem R. M. Meilink; Manon C. deVisser; Anagnostis Theodoropoulos; Michael Fahrbach; Ben Wielstra (Ecology and Evolution)
ABSTRACT We introduce multiplex Kompetitive Allele‐Specific PCR (mxKASP): a modification of “classical” KASP genotyping that allows zygosity to be determined in diploid organisms. Rather than targeting a SNP associated with a single marker, mxKASP targets two non‐homologous markers. We show proof of concept by applying mxKASP to the balanced lethal system in Triturus newts, in which individuals are known to possess either: (1) zero copies of the 1A version of chromosome 1 and two copies of the 1B version; (2) one copy of 1A and one copy of 1B; or (3) two copies of 1A and zero copies of 1B. mxKASP is successful in amplifying both a 1A and a 1B marker in a single reaction (if present), allowing the zygosity of individuals to be inferred. We independently confirm our mxKASP results with a multiplex PCR approach. We argue that mxKASP can be applied to rapidly and economically determine zygostity in diploid organisms, for a large number of samples at once.